Parables of Kierkegaard - Kierkegaard, Søren, 1813-1855 (Book collections on Project MUSE., 1978)
The mind of Kierkegaard has been kept alive in the common memory more by his parables than any other part of his authorship. Like all good parables, they have developed an oral tradition. Do not be surprised if you find here parables that you have heard imperfectly retold or partially revised. Now the reader can track down the original.